2017
DOI: 10.1155/2017/6061042
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Oleaginous Yeast Isolated from Kefir and Its Ability to Accumulate Intracellular Fats in Deproteinated Potato Wastewater with Different Carbon Sources

Abstract: The search for efficient oleaginous microorganisms, which can be an alternative to fossil fuels and biofuels obtained from oilseed crops, has been going on for many years. The suitability of microorganisms in this regard is determined by their ability to biosynthesize lipids with preferred fatty acid profile along with the concurrent utilization of energy-rich industrial waste. In this study, we isolated, characterized, and identified kefir yeast strains using molecular biology techniques. The yeast isolates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 86 publications
(89 reference statements)
0
32
0
Order By: Relevance
“…After 24-h culture in YPD (yeast extract 10 g L −1 , peptone 20 g L −1 , glucose 20 g L −1 ) medium, yeast biomass (2 mL) was centrifuged at 716×g and 4°C for 10 min. DNA from the yeast biomass was isolated following the protocol described by Gientka et al (2017). The internal transcribed spacer (ITS) region was amplified from yeast ribosomal DNA by PCR using primers ITS1 (5′-TCC GTA GGT GAA CCT GCG G-3′) and ITS4 (5′-TCC TCC GCT TAT TGA TAT GC-3′) (White et al 1990).…”
Section: Identification By Dna Restriction Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 24-h culture in YPD (yeast extract 10 g L −1 , peptone 20 g L −1 , glucose 20 g L −1 ) medium, yeast biomass (2 mL) was centrifuged at 716×g and 4°C for 10 min. DNA from the yeast biomass was isolated following the protocol described by Gientka et al (2017). The internal transcribed spacer (ITS) region was amplified from yeast ribosomal DNA by PCR using primers ITS1 (5′-TCC GTA GGT GAA CCT GCG G-3′) and ITS4 (5′-TCC TCC GCT TAT TGA TAT GC-3′) (White et al 1990).…”
Section: Identification By Dna Restriction Analysis Methodsmentioning
confidence: 99%
“…The high C18:1/C18:0 ratios (3.52-3.83) compared with the C16:1/C16:0 ratios (0.03-0.08) during T. domesticum PCM 2960 incubation with DPW may suggest important Δ9 desaturase activity that has a better affinity for fatty acids with 18 carbon atoms than for those with 16 carbon atoms. Makri et al (2010) and Gientka et al (2017) demonstrated a high activity of Δ9 desaturase during the exponential phase of yeast growth. The high levels of C18:1/ C18:0 in Trichosporon lipids on the final culturing day should be explained by the further multiplication of cells.…”
Section: Biomass Yield and Lipid Contentmentioning
confidence: 98%
See 2 more Smart Citations
“…Analysis of the potato wastewater obtained from the process line after the deproteinization stage indicated containing nitrogen and other elements and can be a source of biogenic elements for yeast growth [7,11,17]. Potato wastewater is also a good source of vitamins B 1 , B 2 , B 6 , B 3 /PP, and C, which positively affects the growth of yeast [18].…”
Section: Discussionmentioning
confidence: 99%